Identification of a novel major QTL and F-box candidate genes controlling seed dormancy in common wheat - Yuxia Lyu; Yaoyao Zhao; Wenbo Lu; Xu Pan; Wei Gao; Litian Zhang; Huanfeng Wang; Zhaoyu Yu; Ruihan Wang; Tingfeng Shou; Bingbing Tian; Jiajia Cao; et al. (Theoretical and Applied Genetics, 2026)

Endocrine-driven FGF21 mRNA therapy via route-adaptable lipopolymer nanoparticles for the treatment of pancreatitis - Jia Liu; Ling Zeng; Qian Shen; Tingfeng Yu; Yupeng Ren; Xinxiu Cao; Lingyun Wang; Jinjin Chen (Chemical Engineering Journal, 2025)

Fast and Deterministic Underwater Point Cloud Registration for Multibeam Echo Sounder Data - Liang Zhao; Lan Cheng; Tingfeng Tan; Chun Cao; Feihu Zhang (Journal of Marine Science and Engineering, 2024)
Investigating underwater environments using Multi-Beam Echo Sounder (MBES) point cloud registration technology is a critical yet underdeveloped area in oceanographic research. This paper presents a fast, deterministic Branch-and-Bound (BnB) method with four degrees of freedom, which combines Inertial Measurement Unit (IMU) data with MBES point cloud data for precise registration. Given the prevalence of outliers and noise in underwater acoustic measurements, the BnB method is employed to provide globally deterministic solutions. However, due to the exponential convergence speed of the BnB method with respect to the dimensionality of the solution space, searching within a six-degree-of-freedom parameter space (three rotational and three translational degrees of freedom) can be extremely time-consuming. To this end, the Z-axis of the point cloud is aligned with the gravitational direction of the IMU, reducing the rotational degrees of freedom from three to one, specifically concerning yaw. Additionally, an outlier exclusion strategy is introduced to eliminate mismatches, significantly reducing the number of key-point correspondences and thereby improving registration efficiency. Experiments conducted on both public and real-world lake datasets demonstrate that the proposed method achieves a favorable balance between speed and accuracy, outperforming other tested methods and meeting the demands of contemporary research.

Underwater Gyros Denoising Net (UGDN): A Learning-Based Gyros Denoising Method for Underwater Navigation - Chun Cao; Can Wang; Shaoping Zhao; Tingfeng Tan; Liang Zhao; Feihu Zhang (Journal of Marine Science and Engineering, 2024)
Autonomous Underwater Vehicles (AUVs) are widely used for hydrological monitoring, underwater exploration, and geological surveys. However, AUVs face limitations in underwater navigation due to the high costs associated with Strapdown Inertial Navigation System (SINS) and Doppler Velocity Log (DVL), hindering the development of low-cost vehicles. Micro Electro Mechanical System Inertial Measurement Units (MEMS IMUs) are widely used in industry due to their low cost and can output acceleration and angular velocity, making them suitable as an Attitude Heading Reference System (AHRS) for low-cost vehicles. However, poorly calibrated MEMS IMUs provide an inaccurate angular velocity, leading to rapid drift in orientation. In underwater environments where AUVs cannot use GPS for position correction, this drift can have severe consequences. To address this issue, this paper proposes Underwater Gyros Denoising Net (UGDN), a method based on dilated convolutions and LSTM that learns and extracts the spatiotemporal features of IMU sequences to dynamically compensate for the gyroscope’s angular velocity measurements, reducing attitude and heading errors. In the experimental section of this paper, we deployed this method on a dataset collected from field trials and achieved significant results. The experimental results show that the accuracy of MEMS IMU data denoised by UGDN approaches that of fiber-optic SINS, and when integrated with DVL, it can serve as a low-cost underwater navigation solution.

Underwater Mapping and Optimization Based on Multibeam Echo Sounders - Feihu Zhang; Tingfeng Tan; Xujia Hou; Liang Zhao; Chun Cao; Zewen Wang (Journal of Marine Science and Engineering, 2024)
Multibeam echo sounders (MBESs) enable extensive underwater environment exploration. However, due to weak correlation between adjacent multibeam sonar data and difficulties in inter-frame feature matching, the resulting underwater mapping accuracy frequently falls short of the desired level. To address this issue, this study presents the development of a multibeam data processing system, which includes functionalities for sonar parameter configuration, data storage, and point cloud conversion. Subsequently, an Iterative Extended Kalman Filter (iEKF) algorithm is employed for odometry estimation, facilitating the initial construction of the point cloud map. To further enhance mapping accuracy, we utilize the Generalized Iterative Closest Point (GICP) algorithm for point cloud registration, effectively merging point cloud data collected at different times from the same location. Finally, real-world lake experiments demonstrate that our method achieves an Absolute Trajectory Error (ATE) of 15.10 m and an average local point cloud registration error of 0.97 m. Furthermore, we conduct measurements on various types of artificial targets. The experimental results indicate that the average location error of the targets calculated by our method is 4.62 m, which meets the accuracy requirements for underwater target exploration.

Diversity and novelty of actinobacteria in Arctic marine sediments - Gaiyun Zhang; Tingfeng Cao; Jianxi Ying; Yanliu Yang; Lingqi Ma (Antonie van Leeuwenhoek, 2014)